The Implementation Of Genre-Based Approach In Teaching English At Mtsn 1 Sragen In 2011/2012 Academic Year - Rifa'ah, Hanik; , Prof. Dr. Endang Fauziati, M.Hum; , Dr. Anam Sutopo M.Hum (2013)
This study aims at describing the implementation of Genre-based Approach at MTsN 1 Sragen. The objective of the study is to describe the teaching learning process at MTsN 1 Sragen using Genre-based Approach. The writer applies descriptive qualitative research uses ethnographic study as the type of this research. The data are derived from event, document, and informant. There are three methods of collecting data namely: observation, interview, and document. The techniques for analyzing data are reducing, display, and verifying. The result of this research shows that the goal of teaching English is to enable the students in understanding English as means of communication and active in practicing English. The classroom procedure consists of two patterns. The first patterns are BKOF, MOT, JCOT, and ICOT. The second patterns are BKOF, MOT, and ICOT. The classroom activities consist of the activities during BKOF, namely asking question and giving explanation. The activity during MOT is giving model text. The activity during JCOT is group work and the activities during ICOT are giving task in the classroom and giving the task as homework. The writer also found the strength and the weakness based on the syllabus, indicator, material and classroom procedure. The teacher of MTsN 1 Sragen does not always use the stages of Genre-based Approach in teaching English.